The Enduring Conflict in Somalia: Analyzing the Dynamics of Instability and the Path to Sustainable Peace - Zoia Malik (NUST Journal of International Peace and Stability)
Somalia has faced prolonged instability for over three decades, ranking among the least peaceful nations in the Global Peace Index 2024. This essay examines the origins and dynamics of the Somali conflict, analyzing its historical, political, economic, and social dimensions. Rooted in colonial legacies and clan-based divisions, the conflict intensified under Siad Barre’s authoritarian regime and escalated into civil war following his ousting in 1991. The rise of militant groups like Al-Shabaab, external interventions, and weak governance have further complicated peace efforts. Somalia remains deeply affected by militarization, human displacement, terrorism, and transnational crime, with its economic and social structures in turmoil. Despite some improvements in security indicators, such as a lower terrorism ranking, fundamental challenges persist. The study employs the GPI framework to assess Somalia’s conflict trajectory, highlighting the need for sustained peacebuilding measures. Achieving lasting stability requires addressing both direct violence and structural inequalities to foster national unity and governance reform.